Medication adherence and glycemic control in patients with psychotic disorders in the Veterans Affairs healthcare system - Nelson LA; Graham MR; Lindsey CC; Rasu RS (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
Objective: To compare antihyperglycemic medication adherence and glycemic control between individuals with schizophrenia and related psychotic disorders and a nonpsychiatric comparison group.Methods: This was a retrospective medical record review. A total of 124 subjects with diabetes (62 patients with schizophrenia or a related psychotic disorder and 62 randomly selected, age-matched patients without a psychiatric illness) receiving their medical and psychiatric care exclusively through the Kansas City Veterans Affairs healthcare system during 2008 were included in the study. Adherence to antihyperglycemic and antipsychotic medication was determined by refill records obtained through the computerized patient record system to calculate the cumulative mean gap ratio. Hemoglobin A1C values were utilized to compare glycemic control between groups and compared to glycemic goals established by diabetes treatment guidelines.Results: Antihyperglycemic medication adherence was poor for both groups as approximately 60% of the psychotic disorder group and 75% of the nonpsychiatric comparison group were without antihyperglycemic medication for greater than 30 days during the 12-month period but adherence did not differ between the groups (p=0.182). Antipsychotic adherent subjects (=80% adherent) were more likely to be adherent to their antihyperglycemic medication (p=0.0003). There were no significant differences between groups in glycemic control.Conclusion: Antihyperglycemic medication adherence and glycemic control was less than optimal for both groups. There were no significant differences in antihyperglycemic medication adherence and glycemic control between patients with a psychotic disorder and those without a psychiatric illness.